Results of the distal radius fractures intervened initially by traditional bonesetters - Myderrizi, Neritan (International Journal of Research in Medical Sciences, 2016)
Background: Poor results of the fractures could be result of the intervention of the bone setters. The aim of this study was to analyze functional outcome of the patients intervened initially by a bonesetter. Methods: 179 outpatients with distal radius fractures treated at emergency department of regional hospital of Durres from January 2014 to December 2014 were studied, divided in two groups; presented direct to the hospital (H) and intervened initially by a bonesetter (B). All patient demographics and social data were studied. Anatomic and functional results of the patient were estimated. Results: 179 patients, 114 (63.9%) females with mean age 53.9 years. 115 (64.2%) lived in a rural area. 118 (65.9%) of patients came direct to hospital and 61 (34.1%) were intervened initially by a bonesetter. The mean time of the patients being present to emergency was 1.78±0.8 for group H and 23.6±13.1 for group B. The majority of the fractures are extra articular 108 (60.3%). We had excellent anatomic results in 16 (8.9%), good in 39 (21.8%), fair in 60 (33.5%) and poor in 64 (35.8%). Mean QuickDASH Scores for group H was 50±23 and 80±13 for group B, (p<0.001). Conclusions: Poor functional results come from the distal radius fractures intervened initially by bonesetters. Patients education and dissemination of information about the trauma, trauma system and complication coming from inadequate treatment, will be effective in prevention of complications regarding bonesetter interventions.